2012
DOI: 10.1186/2046-4053-1-20
|View full text |Cite
|
Sign up to set email alerts
|

Auto-titrating versus fixed continuous positive airway pressure for the treatment of obstructive sleep apnea: a systematic review with meta-analyses

Abstract: BackgroundObstructive sleep apnea is a relatively common disorder that can lead to lost productivity and cardiovascular disease. The form of positive airway treatment that should be offered is unclear.MethodsMEDLINE and the Cochrane Central Trials registry were searched for English language randomized controlled trials comparing auto-titrating positive airway pressure (APAP) with continuous positive airway pressure (CPAP) in adults with obstructive sleep apnea (inception through 9/2010). Six researchers extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
96
1
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(107 citation statements)
references
References 35 publications
(98 reference statements)
5
96
1
5
Order By: Relevance
“…However, the levels of adherence in this study are similar to those in other long-term randomized controlled trials. 13,14,32 Furthermore, given our current findings, greater adherence would likely have made the differences in weight between CPAP and Sham even more striking. Second, in comparison to the CPAP group, more participants in the Sham group failed to complete the study.…”
Section: Discussionmentioning
confidence: 69%
“…However, the levels of adherence in this study are similar to those in other long-term randomized controlled trials. 13,14,32 Furthermore, given our current findings, greater adherence would likely have made the differences in weight between CPAP and Sham even more striking. Second, in comparison to the CPAP group, more participants in the Sham group failed to complete the study.…”
Section: Discussionmentioning
confidence: 69%
“…All of our subjects resided in Bangkok or a neighboring province with reported outdoor relative humidity over the year of approximately 80% (according to World Weather & Climate Information, www.weather-andclimate.com. Accessed January 22,2016). This substantially lower average relative humidity was mostly explained by the effect of air conditioners.…”
Section: Discussionmentioning
confidence: 99%
“…However, this improvement may be substantial when compared with autotitrating CPAP, which provides only an additional 11 min compared with conventional fixed-pressure CPAP. 22 Autotitrating CPAP also generally yields a more expensive cost compared with adding heated humidification; in particular, some newer CPAP devices have built-in heated humidification with a cost comparable with that of conventional CPAP. Because our study lasted for only 4 weeks, a study with a longer duration is needed to confirm the clinical benefit and cost-effectiveness of adding heated humidification to CPAP in OSA treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent randomized 6-week trial in almost 200 unselected patients showed a more modest difference in adherence of 0.2 h per night (12 min) and a small difference in sleepiness between APAP and CPAP [20]. Meta-analyses of randomized trials in mostly CPAP naïve patients have consistently shown small but usually statistically significant differences in adherence of 11-14 min per night favoring APAP [21][22][23][24]. A Cochrane review found no difference in residual AHI; however, there was a very small but significant difference in the Epworth Sleepiness Scale of 0.5 points favoring APAP [22].…”
Section: Apap As Treatment For Osamentioning
confidence: 99%